Emergency department resuscitative thoracotomy at an adult major trauma centre: Outcomes following a training programme with standardised indications. (13th May 2020) - Fitzgerald, Mark C; Yong, Matthew S; Martin, Katherine; Zimmet, Adam; Marasco, Silvana F; Mathew, Joseph; Smit, De Villiers; Yeung, Meei; Tan, Gim A; Marquez, Marc; Cheung, Zoe; Boo, Ellaine; et al.
Abstract: Objective: The objective of this study was to report the procedural incidence and patient outcomes after the 2009 introduction of an institutional resuscitative thoracotomy (RT) programme. Emergency physicians, general surgeons and emergency nursing trauma team members were trained to perform RT on thoracic trauma patients with an unresponsive systolic blood pressure (SBP) <70 mmHg within 30 min of arrival, prior to cardiothoracic team back‐up. Methods: A retrospective cohort study was conducted on patients who underwent RT from 2009 to 2017. The primary outcome measures were the incidence of the procedure and patients' survival to hospital discharge. Variables associated with survival were assessed using univariable logistic regression analyses. Results: There were 12 399 major trauma patients, including 7657 with major thoracic trauma and 315 presenting with SBP <70 mmHg. There were 32 RTs performed (incidence of 0.4%; 95% confidence interval [CI] 0.3–0.6) among patients with major thoracic trauma and 10.2% (99% CI 7.3–13.4) among patients with major thoracic trauma and SBP <70 mmHg. There were eight (25%; 95% CI 13.2–42.1) survivors to hospital discharge and no late mortality (mean follow‐up 2.8 years). Survival was significantly associated with the procedure performed within 30 min of arrival (odds ratio 0.09; 95% CI 0.01–0.67) while mortality was associated with the procedure being performed in the setting of traumatic cardiac arrest (odds ratio 18.3; 95% CI 2.4–140.4). Conclusions: A formal training and credentialing programme was associated with a low incidence of the procedure, yet achieved a survival rate of 25%, which is comparable to other reported literature.